Transcatheter arterial chemoembolization combined with PD-1 inhibitors and Lenvatinib for hepatocellular carcinoma with portal vein tumor thrombus - Wu, Hong-Xiao; Ding, Xiao-Yan; Xu, Ya-Wen; Yu, Ming-Hua; Li, Xiao-Mi; Deng, Na; Chen, Jing-Long (World journal of gastroenterology : WJG, 2024)
BACKGROUND Hepatocellular carcinoma (HCC) patients complicated with portal vein tumor thrombus (PVTT) exhibit poor prognoses and treatment responses. AIM To investigate efficacies and safety of the combination of PD-1 inhibitor, transcatheter arterial chemoembolization (TACE) and Lenvatinib in HCC subjects comorbid with PVTT. METHODS From January 2019 to December 2020, HCC patients with PVTT types I-IV were retrospectively enrolled at Beijing Ditan Hospital. They were distributed to either the PTL or TACE/Lenvatinib (TL) group. The median progression-free survival (mPFS) was set as the primary endpoint, while parameters like median overall survival, objective response rate, disease control rate (DCR), and toxicity level served as secondary endpoints. RESULTS Forty-one eligible patients were finally recruited for this study and divided into the PTL (n = 18) and TL (n = 23) groups. For a median follow-up of 21.8 months, the DCRs were 88.9% and 60.9% in the PTL and TL groups (P = 0.046), res-pectively. Moreover, mPFS indicated significant improvement (HR = 0.25; P < 0.001) in PTL-treated patients (5.4 months) compared to TL-treated (2.7 months) patients. There were no treatment-related deaths or differences in adverse events in either group. CONCLUSION A triplet regimen of PTL was safe and well-tolerated as well as exhibited favorable efficacy over the TL regimen for advanced-stage HCC patients with PVTT types I-IV.